Determinan Persalinan oleh Tenaga Kesehatan di Indonesia - Asep Hermawan; Yayi Suryo Prabandari; Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2016)
Determinants of skilled birth attendance in IndonesiaPurposeThis study aimed to find the relationship between health worker ratio with skilled birth attendants (SBA). MethodsThis research was a cross-sectional study using data from Rifaskes 2011 (a nationwide survey of healthcare facilities), SP 2010 (population census), and Riskesdas 2013 (a nationwide survey based on community for basic health). The sample was total population of the district/city as many as 497 districts/cities. The unit of analysis of this study was the district/city in Indonesia. Statistical analysis used univariate analysis, bivariate analysis and generalized linear model (GLM).ResultsThere was no correlation between the ratio of health workers with SBA coverage. But, the GLM analyses showed positive correlation of midwives ratio in the population and SBA when regressed with physicians, nurses, accessibility to community health center (puskesmas) with OR 1.07 (95% CI: 1-1.14), status of region (remote, borderland or islands area) 1.07 (95% CI: 1.01-1.15), and administrative status (district/city) with OR 1.11 (95% CI: 1.03-1.19).ConclusionThe midwives ratio has a strong correlation with SBA after improving accessibility to primary health centers.